Elevated Troponin- Is it Time to Consult A Cardiologist? A Case Series with Review of the Literature - Parajuli, Priyanka; Regmi, Manjari Rani; Lara-Garcia, Odalys Estefania; Maini, Ruby; Bhattarai, Mukul; Deckard, Alan; Kulkarni, Abhishek (Cardiology and Cardiovascular Medicine, 2020)
Cardiac troponin (cTn) is the preferred blood test utilized in the evaluation of acute coronary syndrome (ACS). Elevated cTn represents the presence of myocardial injury but not the cause. As new high sensitivity troponin assays become available, subtle cardiac injuries are being detected. The number of patients encountered with elevated troponin have therefore increased. It is now understood that non-coronary diseases can lead to elevated troponin. There are no specific management guidelines for patients with elevated troponin without a concomitant ACS. Treatment of underlying medical conditions remains the cornerstone of therapy in such patients. Therefore, differentiating elevated troponin secondary to ACS versus non-ACS causes is paramount in order to provide timely and appropriate intervention. In this paper, we discuss a series of cases presenting with elevated troponin, explore non-ACS troponin-elevating conditions along with their underlying pathophysiology, and provide a simple approach to determine the need for cardiology consultation.